2021
DOI: 10.1155/2021/6661937
|View full text |Cite
|
Sign up to set email alerts
|

6-Gingerol, a Major Ingredient of Ginger Attenuates Diethylnitrosamine-Induced Liver Injury in Rats through the Modulation of Oxidative Stress and Anti-Inflammatory Activity

Abstract: Diethylnitrosamine (DEN) is a well-known hepatocarcinogen, and its oral administration causes severe liver damage including cancer. DEN induces the pathogenesis of the liver through reactive oxygen species mediated inflammation and modulation of various biological activities. 6-Gingerol, a major component of ginger, is reported to prevent liver diseases by reducing the oxidative stress and proinflammatory mediators. The present study investigated the hepatoprotective effects of 6-gingerol through the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 56 publications
7
38
0
Order By: Relevance
“…Some previous reports also support that gingerol significantly down-regulated the blood glucose level, creatinine and blood urea nitrogen level in a dose-dependent fashion [35]. Moreover, gingerol role as antioxidant and anti-inflammatory has been proven [38].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Some previous reports also support that gingerol significantly down-regulated the blood glucose level, creatinine and blood urea nitrogen level in a dose-dependent fashion [35]. Moreover, gingerol role as antioxidant and anti-inflammatory has been proven [38].…”
Section: Discussionmentioning
confidence: 70%
“…Taken together, the above results indicated that 6-gingerol treatment ameliorated diabetes-induced inflammatory reaction in kidneys of diabetic rats. Moreover, a previous study reported that gingerol plays a significant role in improving the condition of renal tissue by alteration in p38MAPK and NF-κB activity, and control inflammatory reaction and oxidative stress [38].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione-S-Transferase performs a crucial function in the detoxi cation of many endogenous and xenobiotic compounds (51). In a report, it was revealed that 6-gingerol recovered the activities of GST, SOD, and GSH in diethylnitrosamine (DEN) intoxicated in adult male albino rats (52).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to scavenge 1,1 difenyl-2-picryl-hydrazyl (DPPH) was determined according to our previously published articles with minor modifications. [22,28,29] A 2.5 ml of various dilutions of T-AgNps or extract (100, 200, 300, 400, 500, 600 μg/ml) prepared in methanol was mixed with 1 ml of 0.3 mM methanolic solution of DPPH. After 30 min incubation in darkness and at room temperature, the resultant absorbance was recorded at 517 nm against methanol as a blank.…”
Section: Evaluation Of Free Radical Scavenging Activity By Dpph Methodsmentioning
confidence: 99%